2005
DOI: 10.1590/s1516-35982005000400037
|View full text |Cite
|
Sign up to set email alerts
|

Idade de desmame de cordeiros deslanados para terminação em confinamento, no litoral norte da Bahia

Abstract: RESUMO -Trinta e dois cordeiros (16 machos e 16 fêmeas) deslanados mestiços de Santa Inês, criados com as matrizes em pastagem de Brachiaria humidicola e suplementados em creep-feeding no período noturno, foram distribuídos em delineamento inteiramente casualizado, em esquema fatorial 4x2 -quatro idades de desmame (56, 70, 84 e 98 dias) e sexo, com o objetivo de determinar a melhor idade para o desmame desses animais. Ao desmame, os cordeiros foram confinados, até completarem 126 dias de vida, em baias individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…FREITAS et al (2005) have shown, in Santa Inês hair breed which were weaned at 56 and 98 days, ADG of 143g and 150g in lambs slaughtered at 126 days of age, while MULLER et al (2006) reported ADW of 182 g and 183 in lambs weaned at 35 and 42 days and slaughtered with 28kg of liveweight.…”
Section: Resultsmentioning
confidence: 96%
“…FREITAS et al (2005) have shown, in Santa Inês hair breed which were weaned at 56 and 98 days, ADG of 143g and 150g in lambs slaughtered at 126 days of age, while MULLER et al (2006) reported ADW of 182 g and 183 in lambs weaned at 35 and 42 days and slaughtered with 28kg of liveweight.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, the decision on the most appropriate time and conditions under which weaning should be carried out is of great importance for successfully anticipating weaning (Coimbra Filho, 1992). Different ages have been reported as "ideal" for weaning; earlier literature recommends weaning from 75 to 94 days (Oliveira et al, 1996), but more recent studies have suggested that weaning can be performed earlier at 34, 35, 42, 56 or 62 days (Bôas et al, 2003;Freitas et al, 2005;Müller et al, 2008). However, it is worth noting that the results obtained with different weaning ages depend on nutritional support provided to the animals, and it is essential to supplement infants with use of creep feeding from the second week of life (Siqueira, 2000).…”
Section: Early Weaningmentioning
confidence: 99%
“…On the north coast of Bahia, Santa Inês crossbred lambs were evaluated by Freitas et al (2005) as to the best age for weaning: 56, 70, 84 or 98 days. Lambs were kept with the ewes in Brachiaria humidicola paddocks during the day and were then collected at 5 pm into barns equipped with creep feeders, where lambs had access to a corn and soybean meal concentrate (19% crude protein and 75% TDN).…”
Section: Early Weaningmentioning
confidence: 99%
“…As médias para peso ao nascer encontradas nesse estudo estão próximas aos 3,68 kg e 3,85 kg, registrados pro Freitas et al (2005) Tendo em vista o peso e ganho médios até os 60 dias, Freitas et al (2005) avaliando cordeiros em pastagem e com acesso ao alimento privativo das 17:00 às 7:00 (creep-feeding-noturno), encontraram (P60) de 13,53 kg, com GMD de 0,161. Esses resultados foram muito semelhantes aos encontrados por Siqueira et al (1993) os quais observaram ganhos para SOUZA, A.J.…”
Section: Rebanho 01unclassified